A boron-doped diamond doped sodium-ion battery layered oxide and a preparation method and application thereof

CN122992040APending Publication Date: 2026-10-27NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312197.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0044]1、本发明首次提出使用掺硼金刚石颗粒掺杂NaNi1/3Fe1/3Mn1/3O2(NFM),结合硼掺杂与金刚石掺杂的结构优势,改善NFM材料的性能。掺硼金刚石颗粒不仅有金刚石颗粒坚固的复合骨架,能增强层状氧化物的支撑性能;而且还能在硼元素掺入后,构成[BO3]与[BO4]聚合的三维导电网络结构,打破原有的长程有序排列,从而加速Na+传输。另外,掺硼金刚石颗粒的多孔结构本身能够提供较大的比表面积,能有效缩短Na+的扩散路径,降低离子迁移的动力学势垒,从而提高钠离子层状氧化物的传输速率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992040A_ABST
    Figure CN122992040A_ABST
Patent Text Reader

Abstract

The application provides a boron-doped diamond doped sodium-ion battery layered oxide and a preparation method and application thereof. Specifically, metal oxide, a sodium source and boron-doped diamond are mixed and subjected to ball milling treatment, the obtained slurry is dried, tabletted and then subjected to high-temperature calcination, the calcination product is cooled to 90-110 DEG C, taken out and placed in a protective atmosphere, and a boron-doped diamond doped sodium-ion battery layered oxide is obtained. The application firstly proposes to use boron-doped diamond particles to improve the performance of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 (NFM) material, boron-doped diamond particles are successfully doped into the NFM material crystal phase by using a ball milling method, and the crystal structure is regulated, CV test, EIS impedance spectrum, long cycle test and XRD analysis of the crystal phase are combined, the action mechanism of the boron-doped diamond particles in the charging and discharging process of the sodium-ion battery is revealed, a new doping strategy for improving the sodium-ion layered oxide energy storage mechanism is provided, and the prepared NFM-BDD material has higher specific capacity, higher cycle stability with higher retention rate and lower electrochemical impedance, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy materials and electrochemical energy storage technology, specifically relating to a boron-doped diamond-doped sodium-ion battery layered oxide, its preparation method, and its application. Background Technology

[0002] Under the dual-carbon goal, there is an urgent need for low-cost, high-safety electrochemical energy storage technologies. Lithium-ion batteries have achieved large-scale application; sodium-ion batteries have attracted widespread attention due to their abundant resources, low cost, superior safety, and similar sodium storage mechanism to lithium batteries. The cathode material is the core factor determining the energy density, cycle life, and cost of sodium batteries. Among them, layered transition metal oxides (Na₂O₃) are crucial. x TMO2 is the sodium electrode technology route with the fastest industrialization progress and the highest energy density due to its high energy density, good rate performance, mature process, and great potential for cost reduction.

[0003] In layered oxide systems, the O3 / P2 type NFM system constructed with inexpensive Ni, Fe, and Mn balances cost and electrochemical performance, and is currently a research hotspot. However, NFM materials still face the following technical bottlenecks during charge and discharge: (1) The NFM material has poor structural stability, which triggers irreversible phase transitions in the crystal structure during charge and discharge, ultimately leading to structural collapse; (2) The large Na content + Its radius results in a high diffusion barrier and facilitates the formation of Na. + / Vacation-ordered superstructure generates a voltage plateau and hinders ion transport; (3) A solid electrolyte CEI film is easily formed at the interface between the cathode material and the electrolyte, resulting in increased internal resistance. The above-mentioned technical bottlenecks severely restrict the large-scale commercial application of layered transition metal oxides in sodium-ion batteries.

[0004] Elemental doping is an effective means of solving the above problems. Boron atoms have a small radius, and when boron doping embeds itself into interstitial spaces or replaces some transition metal or oxygen sites in the lattice, it tends to form strong BO bonds with O, constructing a three-dimensional conductive network structure of [BO3] and [BO4] aggregates. This can lock in lattice oxygen and reduce oxygen loss. Simultaneously, strong BO bonds can weaken Na-O interactions, reducing Na... + The migration barrier accelerates ion diffusion, thereby widening the voltage window and increasing the reversible capacity.

[0005] Meanwhile, diamond possesses high elastic modulus, high hardness, and a low coefficient of thermal expansion. It can act as a support for the positive electrode material, buffering the positive electrode active material from the Na+ during charging and discharging processes. + The volumetric strain generated by the insertion / extraction process suppresses the formation of microcracks. In addition, diamond may undergo partial graphitization after heat treatment or carbonization, forming a "diamond-graphite" mixed carbon phase, which has both high conductivity and high stability.

[0006] Boron-doped diamond combines the structural advantages of both boron doping and diamond doping, and theoretically can improve the performance of NFM materials. However, there are currently no known techniques or research reports on using boron-doped diamond to dope NFM materials.

[0007] In view of this, the present invention is hereby proposed. Summary of the Invention

[0008] One objective of this invention is to provide a method for preparing a layered oxide for a boron-doped diamond-doped NFM sodium-ion battery, comprising the following steps:

[0009] (1) Accurately weigh the metal oxide, sodium source and boron-doped diamond according to the stoichiometric ratio, wherein the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1, and the molar stoichiometric ratio of the boron-doped diamond relative to the total amount of Ni, Fe and Mn is 0.01~0.04.

[0010] (2) The raw materials and dispersant from step (1) are subjected to high-energy ball milling, and the slurry obtained from ball milling is dried to obtain a mixed powder;

[0011] (3) After pressing the mixed powder from step (2) into tablets, sinter it at high temperature at 850~1150 °C. When the calcined product is cooled to 90~110 °C, it is taken out and cooled to room temperature under an inert atmosphere to obtain boron-doped diamond-doped NFM sodium-ion battery layered oxide, denoted as NFM-BDD.

[0012] Preferably, in step (1), the sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium oxalate or sodium acetate; the sodium source contains Na element in excess of 3-8% relative to the total molar amount of metal in the metal oxide.

[0013] Preferably, in step (1), the boron-doped diamond has a boron content of 1000~3000 ppm, and the boron-doped diamond is granular with a median particle size D. 50 The value is 0.5~20 µm.

[0014] Preferably, in step (2), the dispersant includes at least one of acetone, ethanol, anhydrous ethanol, isopropanol, n-butanol, or deionized water.

[0015] Preferably, in step (2), the ball-to-material mass ratio of the high-energy ball mill is (2~6):1, the rotation speed is 300~900 rpm, and the milling time is 15~20 h; more preferably, the grinding balls are zirconia balls with a diameter of 3~8 mm.

[0016] Preferably, in step (2), the drying method can be a conventional method known to those skilled in the art, such as placing the slurry in an oven and drying it at 40~60℃ to a constant weight.

[0017] Preferably, in step (3), the specific operation of tableting includes: pressing the mixed powder under a pressure of 5~20 MPa for 5~20 min and forming it.

[0018] Preferably, in step (3), the heating rate of the high-temperature sintering is 2~8 ℃ / min, and the holding time is 10~20h.

[0019] Preferably, in step (3), before the high-temperature sintering, a pre-firing step is also included: specifically, the temperature is raised to 600-800 ℃ at a heating rate of 2-8 ℃ / min and held for 5-7 h.

[0020] Preferably, in step (3), the inert atmosphere is argon or nitrogen.

[0021] The second objective of this invention is to provide a boron-doped diamond-doped NFM sodium-ion battery layered oxide prepared by any of the methods described above.

[0022] A third objective of this invention is to provide a sodium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises a positive current collector and a positive active material layer coated on the surface of the positive current collector, and the positive active material layer comprises a boron-doped diamond-doped NFM sodium-ion battery layered oxide prepared by any of the methods described above.

[0023] Preferably, the positive electrode active material layer comprises the following components: 75-85 parts of boron-doped diamond-doped NFM sodium-ion battery layered oxide, 5-15 parts of conductive agent, and 5-15 parts of binder; more preferably, the conductive agent comprises at least one of acetylene black, SuperP, Ketjen black, carbon nanotubes, graphene, or carbon fiber; the binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, or polytetrafluoroethylene; most preferably, the total weight of the positive electrode active material layer is 100 parts.

[0024] Preferably, the positive current collector is aluminum foil, carbon-coated aluminum foil, or aluminum mesh.

[0025] Preferably, the negative electrode is a sodium electrode with aluminum foil.

[0026] Preferably, the diaphragm is a glass fiber diaphragm, a polypropylene diaphragm, or a polyethylene diaphragm.

[0027] Preferably, the electrolyte comprises an organic solvent, a sodium salt, and optional additives. The organic solvent is a mixed solvent of ethylene carbonate and dimethyl carbonate, the sodium salt is sodium hexafluorophosphate with a concentration of 0.8~1.2 mol / L, and the additive is fluoroethylene carbonate with a content of 1~3 wt%. More preferably, the volume ratio of ethylene carbonate to dimethyl carbonate in the organic solvent is 1:1.

[0028] Preferably, the charge / discharge voltage window of the sodium-ion battery is 1.5~4.5 V; more preferably, the charge / discharge voltage window of the sodium-ion battery is 2.0~4.0 V.

[0029] The fourth objective of this invention is to provide a method for preparing the aforementioned sodium-ion battery, comprising the following steps:

[0030] S1 mixes boron-doped diamond-doped NFM sodium-ion battery layered oxide, conductive agent, binder and solvent, and grinds or stirs to prepare positive electrode slurry;

[0031] S2 involves coating the positive electrode slurry onto the surface of the positive electrode current collector, followed by drying and cutting to obtain the positive electrode sheet;

[0032] S3 In an inert atmosphere, the positive electrode, separator, non-aqueous electrolyte and negative electrode are assembled into a battery.

[0033] Preferably, in step S1, the mass ratio of the boron-doped diamond-doped NFM sodium-ion battery layered oxide, conductive agent, and binder is (75~85):(5~15):(5~15).

[0034] Preferably, in step S1, the conductive agent includes at least one of acetylene black, Super P, Ketjen black, carbon nanotubes, graphene, or carbon fiber; the binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, or polytetrafluoroethylene; and the solvent includes at least one of N-methylpyrrolidone, deionized water, ethanol, or isopropanol.

[0035] Preferably, the grinding or stirring time is 1 to 12 hours, and the stirring speed is 100 to 800 rpm.

[0036] Preferably, in step S2, the positive current collector is aluminum foil, carbon-coated aluminum foil, or aluminum mesh.

[0037] Preferably, in step S2, the drying includes: first placing it in a forced-air drying oven and drying it at 60~100 ℃ for 0.5~1.5 h, and then placing it in a vacuum drying oven and drying it at 100~150 ℃ for 8~16 h.

[0038] Preferably, in step S2, the diameter of the circular piece obtained by cutting the piece is 10~15 mm.

[0039] Preferably, in step S3, the inert atmosphere is argon or nitrogen.

[0040] Preferably, in step S3, the battery is a button cell, a pouch cell, or a prismatic cell; more preferably, the button cell is a CR2032 type button cell.

[0041] Preferably, in step S3, the diaphragm is a glass fiber diaphragm, a polypropylene diaphragm, or a polyethylene diaphragm.

[0042] Preferably, in step S3, the electrolyte comprises an organic solvent, a sodium salt, and an additive; wherein the organic solvent is a mixed solvent of ethylene carbonate and dimethyl carbonate, the sodium salt is sodium hexafluorophosphate, and the additive is fluoroethylene carbonate; more preferably, the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1; in the electrolyte, the concentration of sodium hexafluorophosphate is 0.8~1.2 mol / L, and the content of fluoroethylene carbonate is 1~3 wt%.

[0043] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0044] 1. This invention is the first to propose using boron-doped diamond particles to dope NaNi. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (NFM), combining the structural advantages of boron doping and diamond doping, improves the performance of NFM materials. Boron-doped diamond particles not only possess the robust composite framework of diamond particles, enhancing the supporting performance of layered oxides, but also, after boron incorporation, form a three-dimensional conductive network structure of [BO3] and [BO4] polymers, breaking the original long-range ordered arrangement and thus accelerating the Na... + Transport. Furthermore, the porous structure of boron-doped diamond particles themselves provides a large specific surface area, effectively shortening the Na... + The diffusion path is improved, reducing the kinetic barrier of ion migration and thus increasing the transport rate of sodium ions in layered oxides.

[0045] 2. Based on the concept of boron-doped diamond-doped NFM sodium-ion battery layered oxides, this invention employs ball milling for solid-state synthesis. Specifically, it uses a high-energy ball milling + solid-state sintering process to grind and mix metal oxides, a sodium source, and boron-doped diamond particles in a dispersant, followed by heat treatment to obtain the target product. This two-step synthesis route significantly reduces energy consumption and raw material waste. Simultaneously, the high-energy mechanical ball milling process not only ensures the uniform dispersion of the boron-doped diamond particles in the layered oxide but also induces a large number of defects in the crystal lattice. These defects can serve as nucleation sites during sintering, promoting grain refinement and uniform growth. It should be noted that experiments have shown that prolonged ball milling can lead to excessive amorphization of the material, hindering ion transport and causing mechanical contamination. Therefore, this invention explicitly limits the ball milling time and rotation speed.

[0046] 3. This invention synthesizes a sodium-ion layered oxide cathode material with a boron-doped diamond particle-NF composite structure by incorporating boron-doped diamond particles into NFM material through high-energy ball milling and solid-state sintering. XRD analysis of the crystal phase, combined with CV curve analysis, EIS impedance spectroscopy, and long-cycle testing, reveals the mechanism of boron-doped diamond particles in the charge-discharge process of sodium-ion batteries. This provides a new doping strategy for improving the energy storage mechanism of sodium-ion layered oxides, enhances the electrochemical performance of NFM materials, and has broad application prospects. Attached Figure Description

[0047] To more clearly illustrate the specific embodiments of this application or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0048] Figure 1 This is a schematic diagram of the process flow of the technical solution of the present invention;

[0049] Figure 2 Example 3 of the present invention: NFM-BDD 0.03 Comparative Example 1: NFM CV curves at different scan rates;

[0050] Figure 3 Example 3 of the present invention: NFM-BDD 0.03 EIS curves of NFM and Comparative Example 1;

[0051] Figure 4 Example 3 of the present invention: NFM-BDD 0.03 Compared with the long cycle of NFM in Comparative Example 1;

[0052] Figure 5 Example 3 of the present invention: NFM-BDD 0.03 Charge-discharge curves of NFM at 0.2C for Comparative Example 1;

[0053] Figure 6 Example 3 of the present invention: NFM-BDD 0.03 Comparison with the XRD of NFM in Comparative Example 1. Detailed Implementation

[0054] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0055] Unless otherwise specified, the technical means used in this invention are conventional means well known to those skilled in the art. All raw materials, reagents, instruments, and equipment used in this invention can be purchased commercially or prepared using existing methods. Unless otherwise specified, all reagents used in this invention are of analytical grade. The boron-doped diamond particles used in the embodiments of this invention were purchased from Zhengzhou Smart Industry Co., Ltd., and the mass fraction of boron in the boron-doped diamond particles was 2000 ppm, with a median particle size D. 50 It is 1µm.

[0056] In this invention, the weight parts can be weight units known in the art such as µg, mg, g, kg, or multiples thereof, such as 1 / 10, 1 / 100, 10 times, 100 times, etc.

[0057] Example 1

[0058] (1) Accurately weigh and ball-mill the raw materials: Accurately weigh Na2CO3, NiO, Fe2O3, MnO2 and boron-doped diamond particles according to the stoichiometric ratio. Among them, the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1; the Na element in Na2CO3 is 5% in excess relative to the total molar amount of metal in the metal oxide; the molar stoichiometric ratio of boron-doped diamond relative to the total amount of Ni, Fe and Mn is 0.01, and the particle size is 1µm.

[0059] (2) Ball milling treatment: The weighed raw material is placed in a ball mill jar, and zirconia balls with a diameter of 5 mm are used as grinding balls. The ball-to-material ratio is 4:1. An appropriate amount of anhydrous ethanol is added. Then the ball mill jar is placed in a ball mill. The ball milling speed is 600 rpm and the ball milling time is 17.5 h. After the ball milling is completed, the ball mill jar is placed in an oven and thoroughly dried at 60 ℃.

[0060] (3) Compress and sinter to form layered oxides: Take out an appropriate amount of dried mixed raw materials, grind them into uniform particles with a mortar and pestle, weigh 0.5 g of raw materials and put them into the tableting mold, and let them stand for 10 min under a pressure of 10 MPa.

[0061] The pressed sample was removed from the mold and placed in the crucible. A ceramic boat was placed upside down and centered in the crucible, with the sample symmetrically placed on both sides of the boat, leaning against the crucible wall for support and fixation. The crucible was placed in the center of the muffle furnace, and the temperature parameters were set as follows: the temperature was increased from room temperature to 700 ℃ at a rate of 5 ℃ / min, held for 6 hours, and then increased again from 700 ℃ to 950 ℃ at a rate of 5 ℃ / min, held for 15 hours. Sintering was then completed, and the sample was allowed to cool naturally with the furnace. When the temperature dropped to 100 ℃, the sample was removed and quickly placed in a glove box and stored under an inert atmosphere to obtain a boron-doped diamond-doped NFM sodium-ion battery layered oxide, denoted as NFM-BDD. 0.01 .

[0062] Example 2

[0063] (1) Accurately weigh and ball-mill the raw materials: Accurately weigh Na2CO3, NiO, Fe2O3, MnO2 and boron-doped diamond particles according to the stoichiometric ratio. Among them, the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1; the Na element in Na2CO3 is 5% in excess relative to the total molar amount of metal in the metal oxide; the molar stoichiometric ratio of boron-doped diamond relative to the total amount of Ni, Fe and Mn is 0.02, and the particle size is 1µm.

[0064] (2) Ball milling treatment: The weighed raw material is placed in a ball mill jar, and zirconia balls with a diameter of 5 mm are used as grinding balls. The ball-to-material ratio is 4:1. An appropriate amount of anhydrous ethanol is added. Then the ball mill jar is placed in a ball mill. The ball milling speed is 600 rpm and the ball milling time is 17.5 h. After the ball milling is completed, the ball mill jar is placed in an oven and thoroughly dried at 60 ℃.

[0065] (3) Compress and sinter to form layered oxides: Take out an appropriate amount of dried mixed raw materials, grind them into uniform particles with a mortar and pestle, weigh 0.5 g of raw materials and put them into the tableting mold, and let them stand for 10 min under a pressure of 10 MPa.

[0066] The pressed sample was removed from the mold and placed in the crucible. A ceramic boat was placed upside down and centered in the crucible, with the sample symmetrically placed on both sides of the boat, leaning against the crucible wall for support and fixation. The crucible was placed in the center of the muffle furnace, and the temperature parameters were set as follows: the temperature was increased from room temperature to 700 ℃ at a rate of 5 ℃ / min, held for 6 hours, and then increased again from 700 ℃ to 950 ℃ at a rate of 5 ℃ / min, held for 15 hours. Sintering was then completed, and the sample was allowed to cool naturally with the furnace. When the temperature dropped to 100 ℃, the sample was removed and quickly placed in a glove box and stored under an inert atmosphere to obtain a boron-doped diamond-doped NFM sodium-ion battery layered oxide, denoted as NFM-BDD. 0.02 .

[0067] Example 3

[0068] (1) Accurately weigh and ball-mill the raw materials: Accurately weigh Na2CO3, NiO, Fe2O3, MnO2 and boron-doped diamond particles according to the stoichiometric ratio. Among them, the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1; the Na element in Na2CO3 is 5% in excess relative to the total molar amount of metal in the metal oxide; the molar stoichiometric ratio of boron-doped diamond relative to the total amount of Ni, Fe and Mn is 0.03, and the particle size is 1µm.

[0069] (2) Ball milling treatment: The weighed raw material is placed in a ball mill jar, and zirconia balls with a diameter of 5 mm are used as grinding balls. The ball-to-material ratio is 4:1. An appropriate amount of anhydrous ethanol is added. Then the ball mill jar is placed in a ball mill. The ball milling speed is 600 rpm and the ball milling time is 17.5 h. After the ball milling is completed, the ball mill jar is placed in an oven and thoroughly dried at 60 ℃.

[0070] (3) Compress and sinter to form layered oxides: Take out an appropriate amount of dried mixed raw materials, grind them into uniform particles with a mortar and pestle, weigh 0.5 g of raw materials and put them into the tableting mold, and let them stand for 10 min under a pressure of 10 MPa.

[0071] The pressed sample was removed from the mold and placed in the crucible. A ceramic boat was placed upside down and centered in the crucible, with the sample symmetrically placed on both sides of the boat, leaning against the crucible wall for support and fixation. The crucible was placed in the center of the muffle furnace, and the temperature parameters were set as follows: the temperature was increased from room temperature to 700 ℃ at a rate of 5 ℃ / min, held for 6 hours, and then increased again from 700 ℃ to 950 ℃ at a rate of 5 ℃ / min, held for 15 hours. Sintering was then completed, and the sample was allowed to cool naturally with the furnace. When the temperature dropped to 100 ℃, the sample was removed and quickly placed in a glove box and stored under an inert atmosphere to obtain a boron-doped diamond-doped NFM sodium-ion battery layered oxide, denoted as NFM-BDD. 0.03 .

[0072] Example 4

[0073] (1) Accurately weigh and ball-mill the raw materials: Accurately weigh Na2CO3, NiO, Fe2O3, MnO2 and boron-doped diamond particles according to the stoichiometric ratio. Among them, the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1; the Na element in Na2CO3 is 5% excess relative to the total molar amount of metal in the metal oxide; the molar stoichiometric ratio of boron-doped diamond relative to the total amount of Ni, Fe and Mn is 0.04, and the particle size is 1µm.

[0074] (2) Ball milling treatment: The weighed raw material is placed in a ball mill jar, and zirconia balls with a diameter of 5 mm are used as grinding balls. The ball-to-material ratio is 4:1. An appropriate amount of anhydrous ethanol is added. Then the ball mill jar is placed in a ball mill. The ball milling speed is 600 rpm and the ball milling time is 17.5 h. After the ball milling is completed, the ball mill jar is placed in an oven and thoroughly dried at 60 ℃.

[0075] (3) Compress and sinter to form layered oxides: Take out an appropriate amount of dried mixed raw materials, grind them into uniform particles with a mortar and pestle, weigh 0.5 g of raw materials and put them into the tableting mold, and let them stand for 10 min under a pressure of 10 MPa.

[0076] The pressed sample was removed from the mold and placed in the crucible. A ceramic boat was placed upside down and centered in the crucible, with the sample symmetrically placed on both sides of the boat, leaning against the crucible wall for support and fixation. The crucible was placed in the center of the muffle furnace, and the temperature parameters were set as follows: the temperature was increased from room temperature to 700 ℃ at a rate of 5 ℃ / min, held for 6 hours, and then increased again from 700 ℃ to 950 ℃ at a rate of 5 ℃ / min, held for 15 hours. Sintering was then completed, and the sample was allowed to cool naturally with the furnace. When the temperature dropped to 100 ℃, the sample was removed and quickly placed in a glove box and stored under an inert atmosphere to obtain a boron-doped diamond-doped NFM sodium-ion battery layered oxide, denoted as NFM-BDD. 0.04 .

[0077] Comparative Example 1

[0078] (1) Accurately weigh and ball-mill the raw materials: Accurately weigh the Na2CO3, NiO, Fe2O3 and MnO2 particles according to the stoichiometric ratio. Among them, the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1; the Na element in Na2CO3 is 5% in excess relative to the total molar amount of metal in the metal oxide.

[0079] (2) Ball milling treatment: The weighed raw material is placed in a ball mill jar, and zirconia balls with a diameter of 5 mm are used as grinding balls. The ball-to-material ratio is 4:1. An appropriate amount of anhydrous ethanol is added. Then the ball mill jar is placed in a ball mill. The ball milling speed is 600 rpm and the ball milling time is 17.5 h. After the ball milling is completed, the ball mill jar is placed in an oven and thoroughly dried at 60 ℃.

[0080] (3) Compress and sinter to form layered oxides: Take out an appropriate amount of dried mixed raw materials, grind them into uniform particles with a mortar and pestle, weigh 0.5 g of raw materials and put them into the tableting mold, and let them stand for 10 min under a pressure of 10 MPa.

[0081] The pressed sample was removed from the mold and placed in a crucible. A ceramic boat was placed upside down and centered in the crucible, with the sample symmetrically positioned on either side of the boat, resting against the crucible wall for support and stability. The crucible was placed in the center of a muffle furnace, and the temperature parameters were set as follows: the temperature was increased from room temperature to 700 °C at a rate of 5 °C / min, held for 6 hours, then increased again from 700 °C to 950 °C at a rate of 5 °C / min, held for 15 hours, and sintering was completed. The sample was then allowed to cool naturally with the furnace. When the temperature dropped to 100 °C, the sample was removed and quickly placed in a glove box for storage under an inert atmosphere, yielding NFM sodium-ion battery layered oxide, denoted as NFM.

[0082] Test Example 1

[0083] NFM-BDD prepared according to Examples 1-4 0.01 NFM-BDD 0.02 NFM-BDD 0.03 NFM-BDD 0.04 The NFM prepared in Comparative Example 1 and the NFM prepared in Comparative Example 1 were used as layered oxides to prepare sodium-ion batteries and electrochemical tests were performed. The specific steps included:

[0084] (a) Preparation of sodium-ion battery positive electrode sheet:

[0085] First, the slurry is prepared. The sintered layered oxide (NFM-BDD or NFM) is thoroughly ground in a glove box to a uniform particle size powder. The powder is weighed according to a mass ratio of layered oxide: Ketjen Black conductive agent: PVDF = 8:1:1. The weighed powder is placed in a mortar and ground under an infrared lamp to ensure thorough mixing. An appropriate amount of N-methylpyrrolidone (NMP) is added, and the mixture is slowly stirred at 500 rpm for 6 hours on a magnetic stirrer. The positive electrode is then coated onto the current collector using a coating machine. Carbon-coated aluminum foil is selected as the current collector, and a 150 μm scraper is used to ensure uniform coating of the slurry onto the current collector. The coated electrode is then dried in a forced-air drying oven for 1 hour, followed by transfer to a vacuum drying oven at 120°C for 12 hours, and then allowed to cool to room temperature.

[0086] Next, the electrodes are cut and weighed. The cooled electrodes are removed from the vacuum drying oven and cut into 12mm diameter round pieces. The mass of the electrodes and a current collector of the same size is accurately weighed. The weighed positive electrode is then stored in a glove box.

[0087] (II) Battery Assembly:

[0088] The battery assembly process was carried out in a glove box filled with high-purity argon gas, using CR2032 coin cells for half-cell assembly. The assembly sequence was: positive electrode shell, NFM positive electrode sheet, Whatman glass fiber separator, electrolyte, sodium negative electrode sheet, gasket, spring contact, and negative electrode shell. The electrolyte consisted of a solvent, solute, and additives. The solvent was a mixed solution of EC and DMC (volume ratio 1:1), the solute was NaPF6 at a concentration of 1.0 mol / L, and the additive was fluoroethylene carbonate at a content of 2 wt%. Commercially available sodium negative electrode sheets with aluminum foil were selected.

[0089] (III) Electrochemical Testing:

[0090] Electrochemical performance testing was performed using the CT / CTE-4000 Xinwei Battery Testing System. To ensure the reliability of the test data, all cycle tests were conducted in a constant temperature environment. The test conditions were set as follows: voltage range 2.0-4.0 V, room temperature 25°C, constant current density 1C = 150 mA g. −1 .

[0091] The electrochemical properties of the prepared sodium-ion coin cells were analyzed using a Zahner Zennium electrochemical workstation. Electrochemical impedance spectroscopy (EIS) measurements were performed with a 10 mV AC voltage and a frequency scan range of 100 kHz to 10 mHz.

[0092] The cyclic voltammetry (CV) characteristics and electrochemical properties of the cathode material were analyzed using a CHI760E electrochemical workstation. The analysis was conducted within the range of 0.1–1.0 mV s. −1 The scanning rate range is used.

[0093] (iv) Results and Analysis:

[0094] The electrochemical performance of materials obtained with different doping amounts is shown in Table 1. The initial discharge specific capacity at 0.2C after boron-doped diamond doping ranged from 121.5 mAh / g to 133.7 mAh / g, significantly higher than that of the undoped Comparative Example 1 (113.2 mAh / g). The capacity retention rates after 100 cycles at 1C were 89.2% to 91.2% in the examples and 80.5% to 84.3% after 300 cycles, both significantly higher than that of Comparative Example 1. This indicates that boron-doped diamond doping can effectively improve the discharge specific capacity and suppress capacity decay, especially under long-cycle conditions.

[0095] Table 1

[0096]

[0097] NFM-BDD with the highest initial discharge specific capacity at 0.2C0.03 The following specific research was conducted:

[0098] (1) CV

[0099] At the level of bulk ion migration Figure 2 Variable transmission CV tests show that, under conditions of 0.1 mV s⁻¹, NFM and NFM-BDD 0.03 The oxidation peaks were located at 3.132 V and 3.162 V, respectively, and both showed similar potential shift trends with scan rate across the entire scan range of 0.1–1.0 mV s⁻¹, indicating that their reaction potential responses were not significantly different. In contrast, NFM-BDD 0.03 At all scan rates, the redox peaks were sharper and narrower at half maximum, while NFM showed obvious peak broadening and morphological passivation as the scan rate increased.

[0100] This difference indicates that the main difference between the two systems lies not in the change of potential position, but in the degree of dispersion of the kinetic distribution of the reaction process under rapid charge exchange conditions: the introduction of boron-doped diamond makes the electrochemical reaction exhibit more concentrated kinetic response characteristics, thereby improving the reversibility and process uniformity of the reaction under high-rate conditions.

[0101] (2) EIS

[0102] Figure 3 Electrochemical impedance spectroscopy (EIS) test results show that both exhibit typical characteristics: a semicircle appears in the mid-to-high frequency region, and the low frequency region extends and gradually flattens out. At the high frequency limit, the intersection of the semicircle and the real axis (Z') represents the ohmic resistance (Rs).

[0103] It is worth noting that NFM-BDD 0.03 The Rs value is smaller than that of NFM, indicating that the boron-doped diamond sample has superior ionic conductivity. The semi-circular diameter corresponds to the charge transfer resistance Rct, which is a key parameter characterizing the Faraday reaction kinetics at the electrode-electrolyte interface. NFM-BDD 0.03 The semicircle diameter is significantly smaller than that of NFM, indicating that NFM-BDD 0.03 It exhibits faster interfacial charge transfer kinetics and lower electrochemical reaction energy barriers.

[0104] (3) Long cycle

[0105] NFM-BDD under 1C long cycle 0.03 It exhibits significantly improved reactivity and cycle stability. For example... Figure 4As shown, its initial discharge specific capacity is 124.2 mAh g⁻¹, higher than NFM's 104.4 mAh g⁻¹; after 300 cycles, it still maintains 100.0 mAh g⁻¹, corresponding to a capacity retention of 80.5%, which is significantly better than NFM's 62.7%. This improvement essentially reflects the increased effective activation of the Na⁺ reversible insertion sites in the layered structure after the introduction of boron-doped diamond, thus enhancing the participation of electrochemical reactions.

[0106] Charge-discharge curves at 0.2C ( Figure 5 This indicates that NFM-BDD 0.03 The maximum reversible capacity was 133.7 mAh / g, which is better than the 113.2 mAh / g of NFM material, indicating that the incorporation of boron-doped diamond can improve the reversible specific capacity of layered oxides.

[0107] (4) XRD

[0108] The crystal structures of the samples obtained in Example 1 and Comparative Example 1 were characterized by X-ray diffraction (XRD), and the results are as follows: Figure 6 As shown. NFM and NFM-BDD 0.03 The main diffraction peaks can all be attributed to O3-type α-NaNi 0.5 Mn 0.5 The O2 structure, space group R-3m, matches the standard card PDF#00-054-0887, and no obvious impurity phases were detected, indicating that the sample has good phase purity and crystal structure integrity.

[0109] After boron-doped diamond was used, a distinct main diffraction peak of diamond was detected compared with NFM, corresponding to the standard card PDF#00-006-0675, and NFM-BDD 0.03 The diffraction peaks of the (111) crystal plane shift towards lower Bragg angles and are wider, indicating that after B replaces C atoms in the lattice, the lattice constant increases slightly, causing the diamond diffraction peaks to shift to lower angles. According to Bragg's law, boron-doped diamond has been successfully incorporated into the crystal lattice and has a regulatory effect on the interlayer structure of the material to varying degrees.

[0110] The above research results demonstrate that boron-doped diamond particles significantly affect the phase composition and electrochemical performance of sodium-ion layered oxide (NFM) systems. This invention successfully incorporated boron-doped diamond particles into the crystal phase of NFM materials via ball milling, thereby controlling the crystal structure. Simultaneously, the doping of boron-doped diamond particles enhanced the electrochemical energy storage of NFM materials. The resulting NFM-BDD material exhibits higher specific capacity, higher cycle stability with better retention, and lower electrochemical impedance, demonstrating broad application prospects.

[0111] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A boron-doped diamond-doped sodium-ion battery layered oxide, characterized in that, Includes the following steps: (1) Accurately weigh the metal oxide, sodium source and boron-doped diamond according to the stoichiometric ratio, wherein the molar ratio of Ni, Fe and Mn in the metal oxide is 1:1:1, and the molar stoichiometric ratio of the boron-doped diamond relative to the total amount of Ni, Fe and Mn is 0.01~0.

04. (2) The raw materials and dispersant from step (1) are subjected to high-energy ball milling, and the slurry obtained from ball milling is dried to obtain a mixed powder; (3) After pressing the mixed powder from step (2) into tablets, sinter it at high temperature at 850~1150 °C. When the calcined product is cooled to 90~110 °C, it is taken out and cooled to room temperature under an inert atmosphere to obtain boron-doped diamond-doped NFM sodium-ion battery layered oxide, denoted as NFM-BDD.

2. The method for preparing the boron-doped diamond-doped NFM sodium-ion battery layered oxide as described in claim 1, characterized in that, In step (1), the sodium source includes at least one of sodium carbonate, sodium hydroxide, sodium oxalate or sodium acetate; the sodium source contains Na element in excess of 3-8% relative to the total molar amount of metal in the metal oxide.

3. The method for preparing the layered oxide of boron-doped diamond-doped NFM sodium-ion battery as described in claim 1, characterized in that, In step (1), the boron-doped diamond has a boron content of 1000~3000 ppm, and the boron-doped diamond is granular with a median particle size D. 50 The value is 0.5~20 µm.

4. The method for preparing the layered oxide of boron-doped diamond-doped NFM sodium-ion battery as described in claim 1, characterized in that, In step (2), the dispersant includes at least one of acetone, ethanol, anhydrous ethanol, isopropanol, n-butanol or deionized water; the ball-to-material mass ratio of the high-energy ball mill is (2~6):1, the rotation speed is 300~900 rpm, and the ball milling time is 15~20 h.

5. The method for preparing the boron-doped diamond-doped NFM sodium-ion battery layered oxide as described in claim 1, characterized in that, In step (3), the specific operation of the tableting includes: pressing the mixed powder under a pressure of 5~20 MPa for 5~20 min and pressing it into shape; the heating rate of the high-temperature sintering is 2~8 ℃ / min and the holding time is 10~20 h.

6. The method for preparing the layered oxide of boron-doped diamond-doped NFM sodium-ion battery as described in claim 1, characterized in that, In step (3), before the high-temperature sintering, a pre-firing step is also included: specifically, the temperature is raised to 600-800 ℃ at a heating rate of 2-8 ℃ / min and held for 5-7 h.

7. The boron-doped diamond-doped NFM sodium-ion battery layered oxide prepared by the method according to any one of claims 1-6.

8. A sodium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive electrode sheet includes a positive current collector and a positive active material layer coated on the surface of the positive current collector, wherein the positive active material layer includes the boron-doped diamond-doped NFM sodium-ion battery layered oxide prepared by the method of any one of claims 1-6.

9. The method for preparing a sodium-ion battery as described in claim 8, characterized in that, Includes the following steps: S1 mixes boron-doped diamond-doped NFM sodium-ion battery layered oxide, conductive agent, binder and solvent, and grinds or stirs to prepare positive electrode slurry; S2 involves coating the positive electrode slurry onto the surface of the positive electrode current collector, followed by drying and cutting to obtain the positive electrode sheet; S3 In an inert atmosphere, the positive electrode, separator, non-aqueous electrolyte and negative electrode are assembled into a battery.

10. The method for preparing a sodium-ion battery as described in claim 9, characterized in that, In step S1, the mass ratio of the boron-doped diamond-doped NFM sodium-ion battery layered oxide, conductive agent, and binder is (75~85):(5~15):(5~15); the conductive agent includes at least one of acetylene black, Super P, Ketjen black, carbon nanotubes, graphene, or carbon fiber; the binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, or polytetrafluoroethylene; the solvent includes at least one of N-methylpyrrolidone, deionized water, ethanol, or isopropanol. In step S2, the positive current collector is aluminum foil, carbon-coated aluminum foil, or aluminum mesh; In step S3, the diaphragm is a glass fiber diaphragm, a polypropylene diaphragm, or a polyethylene diaphragm; the electrolyte includes an organic solvent, a sodium salt, and an additive; wherein the organic solvent is a mixed solvent of ethylene carbonate and dimethyl carbonate, the sodium salt is sodium hexafluorophosphate, and the additive is fluoroethylene carbonate.